Stolen words ebook - Florence, Melanie (Second Story Press, 2017)
The story of the beautiful relationship between a little girl and her grandfather. When she asks her grandfather how to say something in his language – Cree – he admits that his language was stolen from him when he was a boy. The little girl then sets out to help her grandfather find his language again. This sensitive and warmly illustrated picture book explores the intergenerational impact of the residential school system that separated young Indigenous children from their families. The story recognizes the pain of those whose culture and language were taken from them, how that pain is passed down, and how healing can also be shared.